EFEKTIFITAS PERUBAHAN POSISI DAN MASSAGE PADA PASEN TIRAH BARING DALAM PENCEGAHAN TERJADINYA DEKUBITUS DI RSUD AL IHSAN KABUPATEN BANDUNG (Jurnal Keperawatan Indonesia Florence Nightingale, 2022)
ABSTRACT Decubitus is a problem that many patients with chronic diseases, patients who are very weak, and paralyzed for a long time face. Decubitus can be prevented, with various actions including by adjusting the position and doing massage. Changing body position can reduce the pressure of continuing to stay in one body position. Generally decubitus sores will occur in the back, buttocks, hips, heels, arms, or spinal area, for this reason massage actions need to be done to improve blood circulation, boost the immune system, and improve the respiratory system. The general objective of this study was to determine the effectiveness of position changes and massage in bed rest patients in preventing decubitus at RSUD Al-Ihsan Kabupaten Bandung. The type of research used is analytic research with a quasi-experimental approach using pre and post test designs. The study population was all bed rest patients treated at Al Ihsan Hospital using an accidental sample. The results showed that position changes in bed rest patients were effective in preventing decubitus at RSUD Al-Ihsan Kabupaten Bandung with a tailed significant value of 0.00 <0.05. Massage performed on bedridden patients is effective in preventing pressure sores, with a tailed significant value of 0.02 <0.05. The action of changing position every 1 hour is more effective than the act of massage every 3 times a day. in treating patients who require bed rest in the prevention of decubitus. Keywords: Change of Position, Massage, bed rest, decubitus